Morpho-functional state of the heart and pulmonary artery pressure in elderly hypertesives with atriall fibrillation - Бевзюк, Любовь Владимировна (ScienceRise: Medical Science, 2016)
The aim: To carry out a comparative study of the structural and functional state of the heart in patients with essential hypertension (EH) depending on the form of atrial fibrillation (AF) - persistent or permanent Methods: Doppler echocardiography, EHRA scale and CHA2DS2VASc. 95 patients aged 60-74 were included in the study, 20 of which with uncomplicated essential hypertension (EH), 39 – with persistent (PersAF) and 36 – permanent (PermAF) atrial fibrillation (AF). Results: as compared with uncomplicated EH, the increase in a degree of left ventricular hypertrophy (LVH) and left atrial size (LA) was found out to be a marker of a diastolic dysfunction of the left ventricle (LV) in AF patients. The highest values of LVH and LA were registered in PermAF. The characteristic PermAF heart rate acceleration appeared to be a significant factor of the heart structure and function changes, notably the increase of LVH and LA dilatation. LV systolic function demonstrated the deterioration in PermAF: along with reduces LV ejection fraction there were 10 % patients with systolic dysfunction. In the majority of AF patients pulmonary hypertension was found: I stage – 51 % in PersAF and 67 % in PermAF; II stage in 5 % and 14 %, respectively. The increase in systolic blood pressure in the pulmonary artery in AF is associated with an increase of right ventricle. Conclusions: Patients with AF have had more apparent structural and functional state of the heart. OP GB further contributes to the disturbance of systolic and diastolic LV function in patients. The increase in diastolic LV dysfunction is associated with increased pressure in the pulmonary artery.